www.parent_child.com an analysis on the parent-child relationship as affected by the child's usage of social networking websites - Castro, Alodia Donabelle Rodriguez
" The Filipino youth's engagement in the phenomenon of online social networking brought by Information Technology and the establishments of its link with the parent-child relationship is an interesting topic of inquiry. Thus, this study explores on the parents' perceptions and reactions on their child's usage of the Internet for social networking. It also looks at the child's reactions regarding his/her parents' perceptions and reactions. Finally, it examines how all of these affect the parent-child relationship. The following theories and/or concepts are used to guide the researchers for this study: Phenomenology, Interactional View, Constructivism, Conversation Analysis and Conversation and Registration Patterns of New Media Information Society. The integration of these helped the researchers in data gathering and analysis of the data. For the quantitative part of this study, the researchers used survey questionnaires and they conducted focus interviews for the qualitative part. Generally, the findings state that the parents regarded Internet-initiated relationships as unstable, do not have a strong foundation and considered as desperate means of getting into a relationship. The parents still prefer the traditional way of building relationships. Parents are willing to negotiate with their child, especially when their wants are in conflict with their child's desires. These negotiations vary from simple errands, career choices, school activities, to relationship involvements. However, the child, although willing to negotiate, would simply choose not to, especially if they think they would not be able to arrive at a compromise. Moreover, the child is somewhat willing to negotiate when their Internet-initiated relationships are at stake. Negotiations involve asking their parent's reasons and justifications why they disagree with their relationships. When their parents fail to give what they think as valid reasons, they just opt to hide their relationships. The child's online social networking activity has only a minimal effect to the parent-child relationship. On informant said that it resulted in her father's jealousy over the guys she meets online. Some said it became their bonding activity. On the one hand, a parent said that her son became more open to her in terms of relationships. On the other hand, children revealed that online social networking gave them more things to hide from their parents."